Vapor Trapping Growth of Single-Crystalline Graphene Flowers: Synthesis, Morphology, and Electronic Properties - Zhang, Yi; Zhang, Luyao; Kim, Pyojae; Ge, Mingyuan; Li, Zhen; Zhou, Chongwu (Nano letters, 2012)
We report a vapor trapping method for the growth of large-grain, single-crystalline graphene flowers with grain size up to 100 μm. Controlled growth of graphene flowers with four lobes and six lobes has been achieved by varying the growth pressure and the methane to hydrogen ratio. Surprisingly, electron backscatter diffraction study revealed that the graphene morphology had little correlation with the crystalline orientation of underlying copper substrate. Field effect transistors were fabricated based on graphene flowers and the fitted device mobility could achieve ∼4200 cm2 V–1 s–1 on Si/SiO2 and ∼20 000 cm2 V–1 s–1 on hexagonal boron nitride (h-BN). Our vapor trapping method provides a viable way for large-grain single-crystalline graphene synthesis for potential high-performance graphene-based electronics.